1980
DOI: 10.1007/bf00421761
|View full text |Cite
|
Sign up to set email alerts
|

Maximal isometric strength and fiber type composition in power and endurance athletes

Abstract: The relationship between maximum isometric strength and muscle fiber type composition was examined in seven endurance and eight power trained athletes. Knee extension strength and ankle extension strength was assessed on 10 separate days and muscle biopsies were taken from the vastus lateralis and gastrocnemius muscles. The percent composition of slow twitch (ST) fibers and fast twitch (FT) fibers was determined from the biopsy samples. Correlation between maximal knee extension strength and percent ST fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…The proportions of FT and ST muscle fibers in the standard model were based on group mean data from Johnson and colleagues, while the proportions of FT fibers in the other two models represented approximately two standard deviations above (FT model) and two standard deviations below (ST model) the mean value for each muscle (Table 2). Despite the small sample size in Johnson et al (n ¼ 6), model fiber type distributions were consistent with muscle biopsy data on sprint athletes (FT model), endurance athletes (ST model), and untrained subjects (standard model) (e.g., Clarkson et al, 1980;Costill et al, 1976;Elder et al, 1982;Gollnick et al, 1972). While individual subjects from any group can certainly have extreme fiber type distributions, our intention was to define models where the percentages of FT and ST fibers represented reasonable group means for the three Penn.…”
Section: Muscle Modelsupporting
confidence: 58%
“…The proportions of FT and ST muscle fibers in the standard model were based on group mean data from Johnson and colleagues, while the proportions of FT fibers in the other two models represented approximately two standard deviations above (FT model) and two standard deviations below (ST model) the mean value for each muscle (Table 2). Despite the small sample size in Johnson et al (n ¼ 6), model fiber type distributions were consistent with muscle biopsy data on sprint athletes (FT model), endurance athletes (ST model), and untrained subjects (standard model) (e.g., Clarkson et al, 1980;Costill et al, 1976;Elder et al, 1982;Gollnick et al, 1972). While individual subjects from any group can certainly have extreme fiber type distributions, our intention was to define models where the percentages of FT and ST fibers represented reasonable group means for the three Penn.…”
Section: Muscle Modelsupporting
confidence: 58%
“…From studies on human subjects it has been suggested that Type II muscle fibres are capable of exerting greater force than are Type I fibres (Komi, Rusko, Vos & Vihko, 1977;Tesch & Karlsson, 1978). In direct contradiction to this finding are the results of Clarkson et al (1980) which appeared to suggest that no significant relationship existed between fibre composition and strength in the knee-extensor muscles, but that a significant negative correlation did exist between strength and the percentage of Type I fibres in the ankle-extensor muscle group. Hulten, Thorstensson, Sjodin & Karlsson (1975) using a two-leg exercise mode, otherwise similar to that employed in the present study, reported that muscle strength was unrelated to muscle fibre composition.…”
Section: Fibre T Ypes and Muscle Strength In Manmentioning
confidence: 93%
“…In order to obtain a group of subjects having the widest possible range of muscle fibre composition, some authors (Clarkson, Kroll & McBride, 1980;Schantz, Randall-Fox, Hutchinson, Tyden & Astrand, 1983) have studied groups of athletic subjects as it is known that elite sprinters tend to have a high proportion of Type II fibres in their leg muscles, whereas in endurance athletes the Type I fibres predominate (Saltin, Henriksson, Nygaard, Andersen & Jansson, 1977). Whilst it is tempting to adopt such a method of selecting subjects to increase the range of the material under study, this practice fails to take account of the specific training programmes of these athletes and of any genetic factors other than muscle fibre composition which may predispose them toward success in their chosen events.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of exercise in this study was adjusted relative to W max , but fat oxidation is more closely related to the anaerobic threshold than to either W max or VO 2max (Fox and Mathews 1981). In addition, as polyathletes the subjects practiced running and cycling endurance activities in varying proportions and their training specificity and the distribution of fiber types in leg muscles may have been distinctly different depending on their training focus (Clarkson et al 1980). Hence differences in adaptive effects of habitual running and cycling schedules on aerobic and fat metabolism (Schneider et al 1990;Achten et al 2003) and differences in IMCL content of different fiber types may have contributed to the disparity in IMCL storage and utilization rates.…”
Section: Intramyocellular Lipid Breakdownmentioning
confidence: 99%